Monetary policy pass-through in Nigeria: An ARDL bound testing approach - Uduak Michael Ekong; Obasi O. Ukoha (Atlantic Review of Economics (ARoEc), 2018)
The paper investigates on the lingering issue of monetary policy transmission from the perspective of Nigeria from 1980 to 2016. Applying a two way techniques of Vector Autoregression and Autoregressive Distributed Lag, we found that (1) jointly considered, monetary policy does not have any long run relationship with economic activity. (2) credit transmission channel is ineffectual in monetary policy transmission in Nigeria. (3) money supply, interest rate and the exchange rate channels are positive channels of monetary policy transmission in Nigeria. Key policy recommendations were monetary policy approach that is more fiscal in nature and instrument specific policies for economic specific issues to grow the country above recessionary growth trajectory.
Keywords: 330; Monetary Policy; Economic activity; Transmission Channels; ARDL; Nigeria